Isoflavones from green vegetable soya beans and their antimicrobial and antioxidant activities. (24th October 2017) - Wang, Taoyun; Liu, Yanli; Li, Xiaoran; Xu, Qiongming; Feng, Yulin; Yang, Shilin
Abstract: BACKGROUND: Green vegetable soya beans, known as Maodou in China, are supplied as vegetable‐type fruits of the soybean plant. Previous study indicated that green vegetable soya beans exhibited antioxidative and anti‐inflammatory activities. However, the material basis and pharmacological activities of green soybean plant were not unravelled clearly. In this study, we investigated the chemical ingredients and their pharmacological activities. RESULTS: Investigation of the chemical ingredients indicated that two new isoflavones, 2′‐hydroxyerythrin A (1 ), and daidzein‐7‐ O ‐ β ‐d ‐6″‐[( E )‐but‐2‐enoyl]glycoside (2 ), together with seven known ones – 7, 4′‐dihydroxy‐6‐methoxyisoflavone (3 ), daidzein (4 ), daidzin (5 ), genistein (6 ), formononetin (7 ), ononin (8 ), and isoerythrinin A (9 ) – were obtained. The structures of compounds1 –9 were elucidated on the basis of spectroscopic and chemical analysis. We evaluated the antimicrobial efficacies and free‐radical scavenging potential of the isolated compounds (1 –9 ). Compounds1 and9 exhibited the most pronounced efficacy against the tested bacterial strains with IC50 values ranging from 10.6 to 22.6 μg mL −1 . The isolated compounds showed moderate radical scavenging properties with compound6 being the most active, followed by compounds3, 1 and4 . CONCLUSIONS: This study indicated that the isoflavones from soya beans could be considered as potential antioxidants or antimicrobials in the food, cosmetics and pharmaceutical industries. © 2017 Society of Chemical Industry